2016
DOI: 10.1007/s10258-016-0115-8
|View full text |Cite
|
Sign up to set email alerts
|

Land reforms and population growth

Abstract: One of the greatest puzzles in demographic history is why in the rich and urbanized England, fertility declined much later than in the poor and rural France. We consider the effects of a land reform on demographic growth by a familyoptimization model where relative per capita wealth generates social status and welfare. We show that tenant farming is the major obstacle to escaping the Malthusian trap with high fertility and low productivity. A land reform provides peasants with higher returns for their investme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…They therefore highlight the tensions between obtaining new freedoms, especially through access to land, and vulnerability to new subsistence vulnerabilities. Similarly, the work of Ulla et al [13], Mizero et al [14] has shown that the internationalization of land reforms limited by the rate of population growth is high. They explain that the active agricultural population participates in the agrarian reform, in the mode of access to land with a view to boosting agricultural growth.…”
Section: Mcda000662 7(3)2020mentioning
confidence: 88%
“…They therefore highlight the tensions between obtaining new freedoms, especially through access to land, and vulnerability to new subsistence vulnerabilities. Similarly, the work of Ulla et al [13], Mizero et al [14] has shown that the internationalization of land reforms limited by the rate of population growth is high. They explain that the active agricultural population participates in the agrarian reform, in the mode of access to land with a view to boosting agricultural growth.…”
Section: Mcda000662 7(3)2020mentioning
confidence: 88%
“…All of these price oscillations, at the micro-level, make planning difficult for all market participants, such as consumers, farmers and import-export and commodity traders, while at the macro-level, unstable agricultural prices affect both developed and developing countries. Xouridas (2015) and Lehmijoki and Palokangas (2016) contended that developed countries are concerned about fiscal and economic exposures to commodity price shocks, whereas developing countries are even more vulnerable to agricultural price volatility because they receive significant income from their commodity export revenues.…”
mentioning
confidence: 99%